'At HIR Owne Discrecion': Women and Will-Making In Late Medieval and Early Tudor Wales*. (1st June 2019) - Youngs, Deborah
The wills of medieval and early Tudor Wales remain underresearched and those made by women are largely unknown. This is unfortunate given their potential to inform our social, cultural and legal histories of Wales. The latter is the focus of this article as it discusses women's roles in the production of the will as a legal document. It begins by showing women's significant contribution to the creation and administration of the will, before analysing the fifty-nine wills that survive from women of Wales, 1382–1550. It explores the circumstances that prompted their writing, the negotiations involved and the different strategies deployed in managing family assets.